Analysis of Diagrid Structure Resist Lateral Forces with Soft Soil Conditions - Akash Sharma; Prof. Surendra Ahirwar (International Journal of Scientific Research in Civil Engineering, 2022)
As India is a developing nation, there is a drastic development taking place in infrastructure and modern living standards, India is number two in population in the world therefore to settle this population there is a high demand of high rise structure, But in India earthquake prone areas where lateral forces are very high there is a requirement of introducing structures with resisting members which can eliminate the failure of the structure due to sudden forces generated by earthquake, thus, the primary target of this study is to decide the effect of seismic forces (Dynamic Analysis) on the high rise structures. Considering Steel diagrid and hybrid diagrid frame at the outer periphery of structure to resist lateral forces, considering seismic zone V with soft type of soil conditions. Comparative study have been made on an unsymmetrical building of G+11 floors considering seismic zone as per I.S. 1893 part 1 2016. For analysis and modeling purpose STAAD.Pro programming is utilized and study is done on the premise of maximum storey displacement, axial forces, shear forces, maximum bending and displacement and most importantly cost analysis of both the structure as per S.O.R. 2017. In this study we adopt 13 loading combination in each case as per Indian Standards and dimensions of column (450 mm x450 mm), beam (400 mm x300 mm) and diagrid (ISMB 100) in all the cases.